'Featured town' fever: The anatomy of a concept and its elevation to national policy in China. (May 2019) - Miao, Julie T.; Phelps, Nicholas A.
Abstract: The suburbanization process worldwide continues to generate significant urban contradictions. Yet the same process also calls forth planning innovations that seek to redress these development challenges. One such in China is the 'Featured Town' policy which has been plucked from its origins in Zhejiang province to national policy prominence. Drawing on a combination of secondary data and original interviews, this paper considers the origins and peculiarities of this planning model, its elevation within national policy and its likely prospects across China. Preliminary findings indicate that the Featured Town policy has fallen foul of many of the complications associated with wider dissemination of locally embedded models. The interlock of local government capitalism and intrapreneurial state is the fundamental driver behind this Featured Town 'fever'.